Assessment of the Correlation between Gender and Third Molar Surgery Duration - Elham Hazeim Abdulkareem; Mohammed Rhael Ali; Sabah Abdul Rasool Hammoodi; Riyam Firas Talib (Wolters Kluwer Medknow Publications, 2022)
Introduction: This study aimed to determine whether there was a difference in the duration it required to extract impacted molars based on the sex of the patient. Methods: In this study, 108 patients with impacted mandibular third molars who attended the Tikrit Dental College (50% of them were men, aged 18-30) were included. The impactions were classified using the Winter's method. The surgery duration was defined as the time between incision and final suturing. Data were analyzed by point-biserial correlation and chi-squared test using R software. Results: The frequencies of different types of impactions were similar between males and females (P ˃ 0.05). The most common type of impaction was mesioangular, followed by distoangular, straight, and horizontal. Negatively very weak correlation found between gender and third molar surgery duration (r = −0.15, P = 0.11, 95% CI −0.037-0.331). Conclusion: No significant correlation among gender and duration of surgery was found. To validate the findings of this study, further research with a larger sample size is needed.